2019
DOI: 10.3390/inventions4020029
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Iridoid Derivatives: Patent Review

Abstract: Iridoids belong to a family of monoterpenoids comprising the cyclopentan[c]-pyran system; this class of compounds offers a wide range of biological effects, namely antileishmanial, anticancer, antiplasmodial, and anti-inflammatory potency. To date, a large number of biologically active iridoid derivatives have been reported from various plant families, including Rubiaceae, Plantaginaceae, Scrophulariaceae, and Verbenaceae. Furthermore, iridoids have the potential to form conjugates with other anticancer, antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Moreover, the information on V. opulus iridoids and their bioactivities is rather scarce. Some iridoids demonstrated remarkable effects against various cancer cells [ 52 ]. It is also worth mentioning that the compounds showing other bioactivities such as antimicrobial and antiviral usually are promising candidates for anticancer agents.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the information on V. opulus iridoids and their bioactivities is rather scarce. Some iridoids demonstrated remarkable effects against various cancer cells [ 52 ]. It is also worth mentioning that the compounds showing other bioactivities such as antimicrobial and antiviral usually are promising candidates for anticancer agents.…”
Section: Resultsmentioning
confidence: 99%
“…From the flow cytometry experiment, it was found that the 1321 cell line treated with filtered leaf extract induced apoptosis, indicating that apoptosis is the mechanism by which the extract caused death of the cancer cells. The anti-cancer property from S. striata can be due to the presence of monoterpenoid compounds such as iridoid glycosides, especially aucubin and catalpol [108]. The compound iridoid glycosides have been known to have anti-cancer properties against various cancer cells, such as breast cancer, renal cancer, and lung cancer [107].…”
Section: Anti-cancer and Anti-tumor Activitymentioning
confidence: 99%
“…[4] The various modifica-tions at the C11 position, including hydrogen, methyl, aldehyde, ester and carboxylic acid, are observed in natural products. [4,7] Structures of catalpol (1) and loganin (2) are depicted as representative carbocyclic iridoids.…”
Section: Structural Classification Of Iridoidsmentioning
confidence: 99%
“…Stereochemical diversity arises from C8 methyl substituents. Nepetalactone (7) and boonein (8) are depicted as a type-II iridoid lactone (Figure 1b-2). While the cis-fused ring system is widely known, trans-fused iridoid lactones are also isolated, such as isoepiiridomyrmecin (9) and epinepetalactone (10) (Figure 1b-3).…”
Section: Structural Classification Of Iridoidsmentioning
confidence: 99%
See 1 more Smart Citation